Effect on disability and safety of Tafamidis in late onset of Met30 transthyretin familial amyloid polyneuropathy. Issue 12 (9th July 2013) - Lozeron, P.; Théaudin, M.; Mincheva, Z.; Ducot, B.; Lacroix, C.; Adams, D.
Abstract : Background and purpose: The aim of this study was to assess the effect of Tafamidis, which slows the progression of early stages of Met30 transthyretin (TTR) familial amyloidosis polyneuropathy (FAP) in more advanced cases. Methods: The study was a prospective, non‐randomized controlled trial carried out at the French national reference centre for FAP with follow‐up at 1 year. Thirty‐seven consecutive Met30‐TTR‐FAP patients were enrolled between December 2009 and July 2011, with NIS‐LL (Neuropathy Impairment Score‐lower limbs) > 10 and Karnofsky score > 60. Their mean (SD) age was 56.4 (19) years. Seventy‐seven per cent of patients had a walking disability. Seven patients (19%) were withdrawn for adverse effects. The primary study outcome measurements, planned before data collection began, were NIS‐LL and NIS‐UL (upper limbs) scores and disability scores. Results: Of the 37 patients entered into the study, 29 were evaluated at 6 months and 13 at 12 months. During the first 6 months of treatment, the mean progression of NIS‐LL score was 4.8 and was similar to that during the period before treatment. Among the 45% of patients without NIS‐LL progression, the NIS‐UL score worsened in 55%. During the first year, 55% deteriorated with respect to disability and 38% with respect to NIS only; only two patients (7%) remained stable. Four (out of 20; 20%) patients who were previously stage 1 reached stage 2 (walking with aid) after this period. Two out of nine patients who were initially normotensive developed orthostatic hypotension. There were a total of 19 adverse events, including four febrile urinary tract infections and three severe diarrhoeas, with faecal incontinence in two. Conclusion: In most patients with advanced Met30 TTR‐FAP, Tafamidis is not able to stop disease progression, in respect of both NIS‐LL and disability. Other anti‐amyloid medicines should be assessed in this context.